Antibiotic prescribing behavior among physicians in Asia: A multinational survey - Wiboonchutikula C. (2023)
Objective: To evaluate antibiotic prescribing behavior (APB) among physicians with various specialties in five Asian countries. Design: Survey of antibiotics prescribing behavior in three stages (initial, on-Treatment, and de-escalation stages). Methods: Participants included internists, infectious diseases (ID) specialists, hematologists, intensivists, and surgeons. Participants' characteristics, patterns of APB, and perceptions of antimicrobial stewardship were collected. A multivariate analysis was conducted to evaluate factors associated with appropriate APB. Results: There were 367 participants. The survey response rate was 82.5% (367/445). For the initial stage, different specialties had different choices for empiric treatment. For the on-Treatment stage, if the patient does not respond to empiric treatment, most respondents will step up to broader-spectrum antibiotics (273/367: 74.39%). For the de-escalation stage, the rate of de-escalation was 10%-60% depending on the specialty. Most respondents would de-escalate antibiotics based on guidelines (250/367: 68.12%). De-escalation was mostly reported by ID specialists (66/106: 62.26%). Respondents who reported that they performed laboratory investigations prior to empirical antibiotic prescriptions (aOR = 2.83) were associated with appropriate use, while respondents who reported ID consultation were associated with appropriate antibiotic management for infections not responding to empiric treatment (aOR = 40.87); adherence with national guidelines (aOR = 2.57) was associated with reported successful carbapenem de-escalation. Conclusion: This study highlights the variation in practices and gaps in appropriate APB on three stages of antibiotic prescription among different specialties. Education on appropriate investigation, partnership with ID specialist, and availability and adherence with national guidelines are critical to help guide appropriate APB among different specialties.